(untitled) (SAARC Journal of Agriculture, 2016)
Turmeric-sesame intercrops at different planting densities were studied at the Regional Agricultural Research Station, Ishwardi, Pabna, Bangladesh in 2014 and 2015 to find out the productivity and economic performance of intercropping sesame with turmeric. The experiment was laid out in RCB design maintaining three replication with five treatments viz., turmeric (100%) + 1 row sesame (33%) in between turmeric lines, turmeric (100%) + 2 row sesame (67%) in between turmeric lines, turmeric (100%) + 3 row sesame (100%) in between turmeric lines, turmeric (100%) + sesame broadcast (100%) in between turmeric lines, sole turmeric and sole sesame. Rhizome yield of turmeric was significantly higher in all intercropping systems (22.85-23.77 t ha-1) than in monoculture system (18.00 t ha-1). The maximum turmeric yield (23.77 t ha-1) was obtained from turmeric (100%) + 3 row sesame (100%) in between turmeric lines intercropping system, which was also exhibited higher turmeric equivalent yield (26.05 t ha-1), benefit cost ratio (3.50), land equivalent ratio (2.28), competitive indices values, SPI (41.09) and MAI (Tk. 294952.62 ha-1) compared to the other intercropping and sole cropping system. SAARC J. Agri., 14(1): 47-58 (2016)